Assessment of the root and canal morphology in the permanent dentition of Saudi Arabian population using cone beam computed and micro-computed tomography - a systematic review - Mohammed Mustafa; Rumesa Batul; Mohmed Isaqali Karobari; Hadi Mohammed Alamri; Abdulaziz Abdulwahed; Ahmed A. Almokhatieb; Qamar Hashem; Abdullah Alsakaker; Mohammad Khursheed Alam; Hany Mohamed Aly Ahmed (BMC, 2024)
Abstract Introduction Root canal treatment procedures require a thorough understanding of root and canal anatomy. The purpose of this systematic review was to examine the morphological differences of teeth root and their canals assessed using cone-beam computed and micro-computed tomography in Saudi Arabian population. Methodology An electronic search was conducted in PubMed / Medline, Scopus, Google Scholar, and Web of Science databases until January 2023 to retrieve related studies. "Root canal morphology," "Saudi Arabia," "Micro-CT," and "cone-beam computed tomography" were used as keywords. A modified version of previously published risk of bias assessment tool was used to determine the quality assessment of included studies. Results The literature search revealed 47 studies that matched the criteria for inclusion, out of which 44 studies used cone beam computed tomography (CBCT) and three were micro-computed tomography (micro-CT) studies. According to the modified version of risk of bias assessment tool, the studies were categorized as low, moderate, and high risk of bias. A total of 47,612 samples were included which comprised of either maxillary teeth (5,412), or mandibular teeth (20,572), and mixed teeth (21,327). 265 samples were used in micro-CT studies while 47,347 teeth samples were used in CBCT studies. Among the CBCT studies, except for three, all the studies were retrospective studies. Frequently used imaging machine and software were 3D Accuitomo 170 and Morita's i-Dixel 3D imaging software respectively. Minimum and maximum voxel sizes were 75 and 300 μm, Vertucci's classification was mostly used to classify the root canal morphology of the teeth. The included micro-CT studies were in-vitro studies where SkyScan 1172 X-ray scanner was the imaging machine with pixel size ranging between 13.4 and 27.4 μm. Vertucci, Ahmed et al. and Pomeranz et al. classifications were applied to classify the root canal morphology. Conclusion This systematic review revealed wide variations in root and canal morphology of Saudi population using high resolution imaging techniques. Clinicians should be aware of the common and unusual root and canal anatomy before commencing root canal treatment. Future micro-CT studies are needed to provide additional qualitative and quantitative data presentations.